IoT Microcontroller Application Prototype as Data Transceiver from Network to USB Device - Rieke Wijayanti; M. Syirajuddin S; Abdul Rasyid; Ahmad Wilda Y (Ikatan Ahli Informatika Indonesia (IAII), 2023)
Telecommunications technology in the early 2000s until now has experienced a rapid increase. Starting with complex devices to microcomputer devices that are able to connect to the network. With the development of networking technology, it will leave behind non-network-support devices that can still be used. The existence of previous research on